Hypopituitarism: genetic, developmental, and acquired etiologies with a focus on the emerging concept of autoimmune hypophysitis - Hironori Bando; Shin Urai; Keitaro Kanie; Masaaki Yamamoto (Endocrine Journal)
Hypopituitarism, characterized by reduced secretion of pituitary hormones, profoundly impacts systemic metabolic homeostasis and quality of life. Its etiology ranges from congenital anomalies in pituitary development to acquired conditions involving inflammation and autoimmune processes. Despite advances in understanding its pathogenesis, diagnostic challenges persist, particularly in cases with complex extra-pituitary manifestations or novel genetic variations. Congenital hypopituitarism often stems from disruptions in transcription factors and signaling pathways critical for pituitary organogenesis. Emerging studies employing next-generation sequencing and developmental biology techniques have revealed new genetic loci and mechanisms implicated in combined pituitary hormone deficiency. However, the pathogenesis of most congenital cases remains elusive, underscoring the need for functional and phenotypic analyses of novel variants. Acquired hypopituitarism, frequently associated with pituitary tumors or systemic diseases, has also been increasingly linked to autoimmune mechanisms. Notably, the concept of paraneoplastic autoimmune hypophysitis has emerged, highlighting malignancy-driven immune responses as a novel etiological framework. Investigations into immune checkpoint inhibitor-related hypophysitis and anti-PIT-1 hypophysitis exemplify the intricate interplay between tumor immunity and endocrine dysfunction, suggesting shared mechanisms involving ectopic antigen expression and autoimmunity. This review synthesizes recent insights into the genetic, developmental, and immunological underpinnings of hypopituitarism. By exploring both congenital and acquired etiologies, we aim to bridge gaps in the current understanding of this complex disorder and provide a foundation for improved diagnostic and therapeutic strategies. Future perspectives emphasize the integration of advanced genetic tools, deeper exploration of tumor-immunity interactions, and a heightened focus on extra-pituitary phenotypes to refine clinical practice and enhance patient outcomes.